UNCTAD III — One more disappointment - Dietrich Kebschull (Intereconomics, 1972)
Early in May the UN Secretary-General, Kurt Waldhelm, felt obliged to Intervene in the proceedings of the Third Conference for Trade and Development. By pointing out that there were no funds available to permit the Conference to extend its work beyond the five weeks that had been planned for it, he destroyed the hopes of all those who had somehow thought that a sixth or seventh week of deliberations would still produce some tangible results.
Keywords: 330; Trade And Development